Russia’s high-tech export during the coronavirus infection spread - S. S. Krasnykh (Вестник университета)
Based on data from the Russian Export Centre, Federal Service for Supervision of Consumer Rights Protection and Human Welfare (Rospotrebnadzor) the article analyses the state of hightech exports of the Russian Federation under restrictive measures related to the spread of coronavirus infection. High-tech exports for the period January 2013 to August 2021 and the number of coronavirus infections for the period March 2020 to August 2021 were used as baseline data. The dynamics and volumes of high-tech exports have been considered, the leading and trailing regions in terms of this indicator have been highlighted. A correlation between the number of coronavirus infection cases and the volume of high-tech exports of the regions of the Russian Federation has been revealed, from which it can be concluded that high-tech exporters have so far managed to adapt to the current coronavirus environment.